UJI AKTIVITAS ANTIBAKTERI ISOLAT SENYAWA GOLONGAN TERPENOID DARI BIJI PEPAYA (Carica papaya L.) TERHADAP Staphylococcus aureus SECARA IN VIVO PADA KELINCI JANTAN - Samsuar Samsuar; Akhmad Rokiban; Adityo Hartono; Ratna Setianingsih (JFL : Jurnal Farmasi Lampung, 2021)
A research on the isolation of terpenoid class of compounds from the seeds of papaya (Carica papaya L.) and test its activity against Staphylococcus aureus in vivo in male rabbits. This research aims to prove that the terpenoid compounds isolated from the seeds of papaya (Carica papaya L.) can inhibit the growth of Staphylococcus aureus in vivo. Separation of terpenoid compounds by column chromatography ((eluent n-hexane: ethyl acetate: ethanol)) resulted in 25 eluates, and then merged based on the results of identification by TLC ((nhexane: ethyl acetate (8: 2)) and the color test reagent Lieburmann -Burchard produce 5 fraction groups. fraction D showed positive terpenoids with Rf 0.75 and the color purple with Lieburmann-Burchard reagent. study using 15 rabbits were divided into 5 groups: P1 (negative control), P2 (positive control) , P3 (5% of the test group), P4 (10% of the test group), P5 (test group 15%). each group was given the intracutaneous Staphylococcus aureus as 0,2ml on the backs of rabbits. Having symptoms of infection each group was given the test substance 3 times a day topically, the observed parameter is the diameter of the wound, and histopathological observations performed on days 3,6 and 9 Analysis of the results of research conducted using ANSIRA showed highly significant differences between groups (p <0.05). Then proceed with the analysis of the results of the analysis HSD test showed highly significant differences in the test group 5% to 10% of the test group and the test group 15%. Isolates terpenoid class of compounds from the seeds of papaya (Carica Papaya L.) with a concentration of 10% and 15% can inhibit the growth of Staphylococcus aureus. Keywords: Antibacterial, Staphylococcus aureus, male rabbits